Should International Classification of Diseases codes be used to survey hospital-acquired pneumonia?. Issue 1 (May 2018) - Wolfensberger, A.; Meier, A.H.; Kuster, S.P.; Mehra, T.; Meier, M.-T.; Sax, H.
Summary: As surveillance of hospital-acquired pneumonia (HAP) is very resource intensive, alternatives for HAP surveillance are needed urgently. This study compared HAP rates according to routine discharge diagnostic codes of the International Classification of Diseases, 10 th Revision (ICD-10; ICD-HAP) with HAP rates according to the validated surveillance definitions of the Hospitals in Europe Link for Infection Control through Surveillance (HELICS/IPSE; HELICS-HAP) by manual retrospective re-evaluation of patient records. The positive predictive value of ICD-HAP for HELICS-HAP was 0.35, and sensitivity was 0.59. Therefore, the currently available ICD-10-based routine discharge data do not allow reliable identification of patients with HAP.